lead-acid batteries

JP2026166101APending Publication Date: 2026-10-14GS YUASA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025058843
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0010】 本開示によれば、鉛蓄電池の深放電サイクルを繰り返す場合に、正極の深放電寿命が向上する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166101000001_ABST
    Figure 2026166101000001_ABST
Patent Text Reader

Abstract

The present invention provides a lead-acid battery in which the deep discharge life of the positive electrode is improved when the deep discharge cycle of the lead-acid battery is repeatedly performed. [Solution] A lead-acid battery 1 comprising a positive electrode plate 3, a negative electrode plate 2, an electrolyte, and a separator 4 interposed between the positive electrode plate and the negative electrode plate, wherein the positive electrode plate includes a positive electrode current collector and a positive electrode material, the positive electrode current collector is made of a lead alloy containing Ca, Sn and Na, and Na forms an intermetallic compound at the grain boundaries of the crystal grains constituting the lead alloy, and the positive electrode material includes fibers, the average fiber diameter of the fibers being 16 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to lead-acid batteries. [Background technology]

[0002] Patent Document 1 describes a lead-acid battery comprising a current collector, a positive electrode plate having a positive electrode material supported by the current collector, and a negative electrode plate, wherein the total pore volume per unit mass of the positive electrode material is 0.167 cm³. 3 The value is less than or equal to / g, and the positive electrode material contains fibers, and the average specific surface area of ​​the fibers measured by the BET method using krypton gas as the adsorption gas is 0.25 m². 2 They are proposing a lead-acid battery that is rated at or above / g.

[0003] Patent Document 2 proposes "an expanded grid for a lead-acid battery using a lead alloy containing 0.05 to 0.09 wt% calcium (Ca), 0.40 to 2.00 wt% tin (Sn), and 0.05 to 0.10 wt% sodium (Na), with the remainder being lead (Pb)." [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2019-67741 [Patent Document 2] Patent No. 3036235 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] In recent years, the load on lead-acid batteries has been increasing due to the advent of vehicles with idle stop-start (ISS) control and OTA (Over The Air) technology. Repeated deep charge-discharge cycles (hereinafter also referred to as "deep discharge cycles") can easily cause softening and detachment of the positive electrode material of lead-acid batteries, shortening the lifespan in deep discharge cycles (hereinafter also referred to as "deep discharge lifespan"). Therefore, it is necessary to improve the durability of the positive electrode material.

[0006] Therefore, in order to improve the durability of the positive electrode material, it has been proposed to add fibers to the positive electrode material (Patent Document 1).

[0007] Furthermore, it has been proposed to use a lead alloy containing Na as the positive electrode current collector (Patent Document 2). Na precipitates at the grain boundaries of the crystal grains, modifying the surface of the positive electrode current collector. The oxide layer formed by this modification wedges into the grain boundaries of the crystal grains, improving the adhesion between the surface of the positive electrode current collector and the positive electrode material. This suppresses the shedding of the positive electrode material, which can improve the deep discharge life of the battery.

[0008] However, when an alloy containing sodium (Na) is used for the positive electrode current collector, the deposition of Na on the current collector surface accelerates the deterioration of the fibers. Specifically, the Na deposited on the current collector surface reacts with moisture to produce sodium hydroxide (NaOH). When this NaOH dissolves in the electrolyte, the pH of the electrolyte rises, creating an alkaline environment, which is thought to accelerate the hydrolysis of the fibers and lead to fiber deterioration. This phenomenon can occur during the maturation drying process in the manufacturing of the positive electrode plate, during storage of the positive electrode plate, and after the electrolyte is injected. The thinner the fiber diameter, the greater the fiber deterioration, making it difficult to obtain the desired effect of the fibers. [Means for solving the problem]

[0009] One aspect of the present disclosure relates to a lead-acid battery comprising a positive electrode plate, a negative electrode plate, an electrolyte, and a separator interposed between the positive electrode plate and the negative electrode plate, wherein the positive electrode plate includes a positive electrode current collector and a positive electrode material, the positive electrode current collector is composed of a lead alloy containing Ca, Sn, and Na, the Na forms an intermetallic compound at the grain boundaries of the crystal grains constituting the lead alloy, and the positive electrode material includes fibers, the average fiber diameter of the fibers being 16 μm or less. [Effects of the Invention]

[0010] According to this disclosure, the deep discharge life of the positive electrode is improved when the deep discharge cycle of a lead-acid battery is repeated. [Brief explanation of the drawing]

[0011] [Figure 1] This is a partially cutaway perspective view showing the external appearance and internal structure of a lead-acid battery according to one embodiment of the present invention. [Modes for carrying out the invention]

[0012] The embodiments of this disclosure will be described below with examples, but this disclosure is not limited to the examples described below. In the following description, specific numerical values ​​and materials may be given as examples, but other numerical values ​​and materials may be applied as long as the effects of this disclosure are obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "greater than or equal to numerical value A and less than or equal to numerical value B". In the following description, when lower and upper limits of numerical values ​​relating to specific physical properties or conditions are given as examples, either of the given lower limits and either of the given upper limits can be arbitrarily combined, as long as the lower limit is not greater than or equal to the upper limit. When multiple materials are given as examples, one of them may be selected and used alone, or two or more may be used in combination.

[0013] Furthermore, the present disclosure encompasses combinations of the matters recited in two or more claims arbitrarily selected from the plurality of claims recited in the appended claims. That is, as long as no technical contradiction arises, the matters recited in two or more claims arbitrarily selected from the plurality of claims recited in the appended claims may be combined.

[0014] (1) A lead-acid battery according to the present embodiment (hereinafter also referred to as "lead-acid battery (B)") includes a positive electrode plate, a negative electrode plate, an electrolytic solution, and a separator interposed between the positive electrode plate and the negative electrode plate, wherein the positive electrode plate includes a positive electrode current collector and a positive electrode material. The positive electrode current collector is composed of a lead alloy containing Ca, Sn and Na, and Na forms an intermetallic compound at the grain boundaries of the crystal grains constituting the lead alloy. The positive electrode material contains fibers, and the average fiber diameter of the fibers is 16 μm or less. Hereinafter, the lead alloy containing Ca, Sn and Na, in which Na forms an intermetallic compound at the grain boundaries of crystal grains, is also referred to as "lead alloy (NA)".

[0015] In the lead-acid battery (B) described in (1) above, the binding force between the positive electrode materials is significantly enhanced by the fibers. Therefore, even when deep discharge cycles of the battery are repeated, softening and shedding of the positive electrode material are suppressed, and the battery can ensure favorable life performance. The life performance of the battery when deep discharge cycles are repeated (hereinafter also referred to as "deep discharge life") can be evaluated by the "life test method" described later.

[0016] In the charged state, the positive electrode material forms a network in which lead dioxide particles are bonded to each other. When lead dioxide is converted to lead sulfate by a discharge reaction, its volume expands by about 1.5 times. When deep discharge cycles are repeated, the bonds between the lead compound particles contained in the positive electrode material are normally broken, and a part of the lead compound becomes isolated. As a result, softening progresses from the surface of the positive electrode plate, and shedding of the positive electrode material occurs. In order to suppress such softening and shedding, it is considered necessary that the contact area between the fibers contained in the positive electrode material and the positive electrode material is sufficiently large.

[0017] Based on the finding that the thinner the fiber diameter, the larger the contact area between the lead compound constituting the positive electrode material and the fiber, and the greater the effect of suppressing softening and detachment of the positive electrode material by the fiber, the positive electrode material of lead-acid battery (B) contains fibers with an average fiber diameter of 16 μm or less. When the average fiber diameter of the fibers is 16 μm or less, the specific surface area of ​​the fibers becomes very large, and the contact area between the fibers and the lead compound becomes large. It is thought that the entanglement of the fibers and the lead compound over a large contact area increases the binding force between the lead compounds, and the deep discharge life of lead-acid battery (B) is significantly improved. The average fiber diameter of the fibers may be 15 μm or less, or 14 μm or less, 13 μm or less, 12 μm or less, or 11 μm or less.

[0018] However, when an alloy containing sodium (Na) is used for the positive electrode current collector, the degradation of the fibers is usually accelerated by the Na deposited on the current collector surface. The thinner the fiber diameter, the greater the degree of fiber degradation, making it difficult to obtain the desired effect of the fibers. This is because the deposition of Na creates a localized alkaline environment in the electrolyte, causing the fibers to corrode (degrade) due to the alkali, gradually thinning and becoming brittle. In that case, the effect of the fibers in maintaining the bonding between lead compounds is lost.

[0019] In contrast, in the lead alloy (NA) that constitutes the positive electrode current collector, an intermetallic compound containing Na is formed, so even when using fibers with very small fiber diameters, fiber degradation is suppressed. As a result, it becomes possible to obtain both the effect of improving the durability of the positive electrode material due to the fibers and the effect of improving the durability of the positive electrode material due to the lead alloy (NA). This significantly improves the deep discharge life of the battery. When an intermetallic compound containing Na is formed, Na is bound to Pb, Sn, etc., and does not separate from the lead alloy, so the diffusion and movement of Na is suppressed. Therefore, the deposition of Na on the surface of the current collector is suppressed, and the fibers near the current collector are less likely to degrade, which suppresses the embrittlement of the positive electrode material near the current collector, and it is thought that the decrease in adhesion between the positive electrode current collector and the positive electrode material is significantly suppressed.

[0020] In lead alloys (NA), Ca can improve the mechanical strength of the lead alloy. Sn can improve the corrosion resistance of the lead alloy. Na exhibits a high precipitation hardening phenomenon. Due to the precipitation hardening phenomenon, the lead alloy becomes harder. Therefore, lead alloys (NA) are less susceptible to deformation due to corrosion.

[0021] The improvement in hardness of lead alloys is brought about by the precipitation of fine particles of intermetallic compounds at the grain boundaries of the crystal grains. Among these, intermetallic compounds containing sodium (Na) have been found to have a particularly large effect in improving the hardness of lead alloys. Examples of intermetallic compounds containing Na include intermetallic compounds containing Na and Pb, and intermetallic compounds containing Na and Sn (Na-Sn compounds). Na-Sn compounds may have a composition such as NaSn6.

[0022] Lead alloys (NA) may also be synthesized by first synthesizing a Pb-Ca-Sn alloy, and then further alloying the Pb-Ca-Sn alloy with Na. In this case, the Ca contained in the Pb-Ca-Sn alloy promotes the formation of intermetallic compounds containing Na. For example, intermetallic compounds containing Na can be formed when Ca in the Pb-Ca-Sn alloy is substituted with Na. Na that does not form intermetallic compounds tends to gradually detach from the lead alloy and precipitate on the lead alloy surface. Such Na not only cannot exhibit the precipitation strengthening phenomenon, but can also promote the corrosion of the lead alloy.

[0023] Intermetallic compounds containing sodium (Na) are difficult to synthesize using simple methods such as mixing and melting starting materials and then solidifying the molten metal, due to their low bond energy. This is thought to be related to the fact that the equilibrium constant for the formation reaction of Na-containing intermetallic compounds is very small compared to the equilibrium constants for the formation reactions of other intermetallic compounds that can be formed. For example, the equilibrium constant for the formation reaction of intermetallic compounds containing Ca and Sn (Ca-Sn compounds) is overwhelmingly larger than the equilibrium constant for the formation reaction of Na-Sn compounds. Therefore, in the presence of Ca, Na-Sn compounds are not formed. In contrast, when Ca is replaced with Na after forming a Pb-Ca-Sn alloy, the formation of Na-containing intermetallic compounds can proceed. This is thought to be because, under conditions where fine particles of Na-containing intermetallic compounds can grow large, the Na-containing intermetallic compounds can be stabilized.

[0024] Furthermore, the Pb-Ca-Sn alloy used for the substitution reaction with Na may also contain Na. Alternatively, lead alloy (NA) can be produced by mixing a large amount of Na into the starting materials beforehand, melting the molten metal, allowing it to solidify, and then melting it again. In this case, a large amount of Na is required because lead and Na have a low affinity.

[0025] (2) In the lead-acid battery (B) described in (1) above, the average fiber diameter of the fibers is preferably 10 μm or less.

[0026] In the lead-acid battery (B) described in (2) above, when the average fiber diameter of the fibers is reduced to 10 μm or less, the fibers have a large specific surface area, which increases the contact area between the lead compound constituting the positive electrode material and the fibers. As a result, the effect of improving the bonding strength between the positive electrode materials by the fibers is greatly increased.

[0027] In the lead-acid battery (B) described in (2) above, the average fiber diameter of the fibers may be 9 μm or less. From the viewpoint of ensuring sufficient strength of the fibers themselves, the average fiber diameter of the fibers is preferably 0.1 μm or more, and may also be 0.5 μm or more. The average fiber diameter of the fibers can be controlled during the fiber synthesis process.

[0028] (3) In the lead-acid battery (B) described in (1) or (2) above, the average fiber diameter of the fibers is preferably 1 μm to 8 μm.

[0029] In the lead-acid battery (B) described in (3) above, when the average fiber diameter of the fibers is in the range of 1 μm to 8 μm, the fibers have a larger specific surface area, thus increasing the contact area between the lead compound constituting the positive electrode material and the fibers. Furthermore, by making the average fiber diameter of the fibers 1 μm or more, higher strength of the fibers can be ensured. This further enhances the effect of the fibers on improving the bonding strength between the positive electrode materials.

[0030] In the lead-acid battery (B) described in (1) or (2) above, the average fiber diameter of the fibers may be in the range of 0.1 μm to 16 μm, 0.5 μm to 12 μm, 1.0 μm to 8 μm, or 2 μm to 8 μm.

[0031] (4) In the lead-acid battery (B) described in any one of (1) to (3) above, it is preferable that the surface of the fiber has irregularities. Furthermore, it is preferable that the irregularities on the surface of the fiber are formed along the circumferential direction of the fiber. The circumferential direction of the fiber is any direction that intersects the longitudinal direction of the fiber. Such a direction is, for example, a direction that has an angle of 45° or more on average with the longitudinal direction of the fiber.

[0032] In the lead-acid battery (B) described in (4) above, the friction between the lead compound particles and the fibers is increased by the surface irregularities of the fibers. In particular, when the surface irregularities of the fibers are formed along the circumferential direction of the fibers, the friction is greater when the lead compound particles try to move in the longitudinal direction of the fibers. Therefore, an effect is obtained in which the expansion of the positive electrode material along the longitudinal direction of the fibers is suppressed.

[0033] In the lead-acid battery (B) described in (4) above, the surface irregularities of the fibers may be formed in a ripple-like pattern along the circumferential direction of the fibers. The trajectory of the ripple-like irregularities extending on the surface of the fibers is long, and the shape of the irregularities is complex. Therefore, such irregularities are likely to engage with particles of the lead compound that are trying to move in the longitudinal direction of the fibers. Thus, the effect of suppressing the expansion of the positive electrode material along the longitudinal direction of the fibers is further enhanced.

[0034] The irregularities may be formed on the fibers beforehand, or they may be formed on smooth fibers by a predetermined method, or they may be formed during the manufacturing process of the lead-acid battery. One method for forming irregularities on the surface of fibers is chemical treatment, which modifies the fiber surface using chemicals such as acids and alkalis. Other methods for forming irregularities on the surface of fibers include plasma treatment, which modifies the fiber surface using plasma, corona treatment, which modifies the fiber surface using high-voltage discharge, and UV irradiation treatment, which modifies the fiber surface using ultraviolet light. Yet another method is sandblasting, for example. Sandblasting is a process in which fine powder harder than the fiber is impacted onto the fiber.

[0035] When using methods such as plasma treatment, corona treatment, or UV irradiation to create irregularities on fibers, the state of the irregularities may be altered by changing the output value of the processing device, the processing time, or both. In sandblasting, the speed of the fine powder impacting the fibers and the processing time can also be changed.

[0036] (5) In the lead-acid battery (B) described in (1) above, the intermetallic compound preferably contains a Na-Sn compound. In the lead-acid battery (B) described in (5) above, the lead alloy (NA) is less susceptible to deformation due to corrosion, thereby significantly improving the durability of the positive electrode.

[0037] Compared with other intermetallic compounds, the Na-Sn compound has a relatively large particle size of particles precipitated at the grain boundaries of crystal grains. As a result, the Na-Sn compound has high stability, and precipitation strengthening by the Na-Sn compound is significantly exhibited. That is, when fine particles of the Na-Sn compound precipitate at the grain boundaries of the crystal grains constituting the lead alloy (NA), deformation due to corrosion is significantly suppressed. The reason why the particle size of the Na-Sn compound increases is that the melting point of the Na-Sn compound is low. It is considered that a compound with a low melting point is likely to grow to a large particle size because it crystallizes gradually over time.

[0038] The presence of the Na-Sn compound in the lead alloy (NA) can be confirmed by, for example, SEM-EDS (energy dispersive X-ray spectroscopy). According to SEM-EDS, element maps (distribution diagrams of characteristic X-rays) of various elements can be obtained in a cross-sectional SEM image of the lead alloy. When characteristic X-rays of Na and Sn are respectively detected at the same position in the cross-sectional SEM image, it can be determined that the Na-Sn compound is present at that position on the cross section of the lead alloy. The presence of other intermetallic compounds can also be confirmed by a similar method.

[0039] The cross-sectional SEM image of the lead alloy may be measured after forming a cross section of the lead alloy and processing the cross section with a cross-section polisher (CP). An example of the measurement conditions is shown below. <CP Processing Conditions> Equipment used: IB-19520CCP manufactured by JEOL Ltd. Acceleration voltage: 4 kV Cooling temperature: -100°C <SEM Observation> Equipment used: JSM-IT500HR / LA (Scanning Electron Microscope) manufactured by JEOL Ltd. Acceleration voltage: 5 kV Magnification: 30 to 7000 times <eds> Equipment used: JEOL Ltd. JSM-IT500HR / LA (Scanning Electron Microscope) Acceleration voltage: 5kV, 2kV Magnification: 20000~600000x

[0040] (6) In the lead-acid battery (B) described in (5) above, it is preferable that at least three Na-Sn compound particles are detected at each grain boundary of a single crystal grain observed in the cross-section of the lead alloy (NA).

[0041] A grain boundary of a single crystal grain refers to the total length of each closed grain boundary observed in the cross-section of a lead alloy. Each region enclosed by an individual closed grain boundary corresponds to a single crystal grain. Na-Sn compound particles precipitate at the grain boundaries. By counting the number of Na-Sn compound particles along the total length of 10 or more non-adjacent closed grain boundaries and averaging these particle counts, the number of Na-Sn compound particles present per grain boundary of a single crystal grain (hereinafter also referred to as "particle number (N)") can be obtained. The particle number (N) may be 5 or more. Preferably, the particle number (N) is less than 100, preferably 20 or less, may be 10 or less, and more preferably less than 10. Furthermore, it is preferable that the number of grain boundaries with a particle number (N) of 5 or more is more than half of the total number of grain boundaries measured.

[0042] In the lead-acid battery (B) described in (6) above, a sufficient number of Na-Sn compound particles are deposited at the grain boundaries, resulting in even more pronounced precipitation reinforcement by the Na-Sn compound. Therefore, deformation due to corrosion is further suppressed, and the durability of the positive electrode can be further improved. As a result, the deep discharge life of the battery can be further improved.

[0043] (7) In the lead-acid battery (B) described in (5) or (6) above, the particle size of the Na-Sn compound particles is preferably 50 nm or more and 800 nm or less. More preferably, the particle size of the Na-Sn compound particles may be 100 nm or more and 700 nm or less, or 100 nm or more and 600 nm or less.

[0044] One reason why intermetallic compounds containing sodium (Na) have a significant effect in improving the hardness of lead alloys (NA) is that the particle size of Na-containing intermetallic compounds tends to be larger. For example, the particle size of Na-Sn compounds tends to be several hundred nanometers, while that of Ca-Sn compounds tends to be several tens of nanometers. It is thought that the larger the precipitate of the intermetallic compound, the greater the effect in improving the hardness of lead alloys (NA).

[0045] The bond energy of intermetallic compounds containing the monovalent metal Na is thought to be lower than that of intermetallic compounds containing the divalent metal Ca. Compounds with high bond energy can exist stably even when the particle size is small and the surface energy is high, whereas compounds with low bond energy are thought to be unable to be stabilized unless the particle size is large and the surface energy is low. In other words, since the fine particles of intermetallic compounds containing Na tend to be large, Na is thought to have a significant effect in improving the hardness of lead alloys (NA).

[0046] The particle size of Na-Sn compounds can be determined by identifying all Na-Sn compound particles at the grain boundaries of arbitrarily selected crystal grains in a cross-sectional SEM image of lead alloy (NA) (or an elemental map of Na and Sn based on such a cross-sectional SEM image), measuring their maximum diameters, and averaging the results. A similar measurement is then performed at the grain boundaries of 10 or more arbitrarily selected crystal grains, and the average values ​​of these 10 or more measurements are further averaged to obtain the particle size of the Na-Sn compound.

[0047] In the lead-acid battery (B) described in (7) above, the particle size of the Na-Sn compound particles is considered to be within a range in which the precipitation strengthening phenomenon is likely to occur. Therefore, the desired effect can be obtained more reliably. When the particle size of the Na-Sn compound particles is 50 nm or larger, the precipitation strengthening effect becomes even greater. Furthermore, it is preferable to set the particle size of the Na-Sn compound particles to 800 nm or less, as this makes it less likely for localized stress concentration that leads to corrosion to occur.

[0048] (8) In the lead-acid battery (B) described in (5) above, the mass content C of Na contained in the lead alloy (NA) Na Preferably, the amount is 10 ppm or more and 100 ppm or less. More preferably, the mass content of Na contained in the lead alloy (NA) is C Na A concentration of 20 ppm or more but less than 100 ppm (especially 90 ppm or less) is preferable, but 30 ppm or more but 80 ppm or less is also acceptable, and 40 ppm or more but 70 ppm or less is also acceptable.

[0049] In the lead-acid battery (B) described in (8) above, Na can stably exist in the lead alloy (NA) as a constituent element of the intermetallic compound. Therefore, a precipitation strengthening phenomenon occurs over the long term, and the lead alloy (NA) hardens. Consequently, the lead alloy (NA) is less susceptible to deformation due to corrosion.

[0050] (9) In the lead-acid battery (B) described in (5) above, the lead alloy (NA) either does not contain Bi, or if it contains Bi, the mass content of Bi C Bi However, it is preferable that it be less than 0.03% by mass. More preferably, the mass content of Bi in the lead alloy (NA) C Bi The mass content of Bi in lead alloy (NA) C is 0.02% by mass or less, and more preferably 0.01% by mass or less. Bi This may be 0.001% by mass or more, or 0.005% by mass or more.

[0051] In the lead-acid battery (B) described in (9) above, the lead alloy (NA) has good processability despite its high hardness. Therefore, the lead alloy (NA) is suitable as a material for a positive electrode current collector (expanded grid) formed by, for example, expansion processing. However, if the lead alloy (NA) contains a large amount of Bi, Bi-Na intermetallic compounds tend to be preferentially formed, which tends to reduce the processability of the lead alloy (NA). Bi mass content C Bi By keeping the amount below 0.03 mass%, the formation of Bi-Na intermetallic compounds is suppressed, resulting in improved workability (especially ductility) of the lead alloy (NA).

[0052] (10) In the lead-acid battery (B) described in the above (5), the mass content C of Sn contained in the lead alloy (NA) Sn may be, for example, 1.5 mass% or more and 2.5 mass% or less. The mass content C of Sn contained in the lead alloy (NA) Sn may be 1.6 mass% or more and 2.3 mass% or less, or 1.7 mass% or more and 2.2 mass% or less.

[0053] In the lead-acid battery (B) described in the above (10), since the lead alloy (NA) contains Sn within the above range, the corrosion resistance is further excellent.

[0054] The mass content of each element other than lead contained in the lead alloy can be analyzed, for example, in accordance with the lead separation inductively coupled plasma optical emission spectrometry described in JIS H2105. Specifically, a part of the lead alloy having metallic luster is collected as a sample, the sample is decomposed with tartaric acid and dilute nitric acid to obtain an aqueous solution. Hydrochloric acid is added to the aqueous solution to precipitate lead chloride, followed by filtration, and the filtrate is collected. Thereafter, it can be determined by measuring the emission intensity of each element in the solution by ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy) using an ICP optical emission spectrometer (for example, ICPS-8000 manufactured by Shimadzu Corporation). The mass of each element contained in the solution is determined using a previously prepared calibration curve. The ratio of the obtained mass of each element to the mass of the lead alloy sample subjected to the analysis is determined as the mass content of each said element.

[0055] (11) In the lead-acid battery (B) described in the above (1), the positive electrode current collector may be an expanded grid.

[0056] In the lead-acid battery (B) described in the above (11), since the expanded grid is manufactured from the lead alloy (NA) which has good workability despite high hardness, the expanded grid with high hardness has small strain, and deformation and progression of corrosion caused by strain are easily suppressed. That is, the effect of suppressing corrosion and deformation of the lead alloy (NA) is easily manifested when used as a material for an expanded grid.

[0057] The lead-acid battery (B) relating to this disclosure may be a valve-regulated lead-acid battery (VRLA type battery) or a liquid-type battery (vented type battery).

[0058] A lead-acid battery (B) comprises a positive electrode plate, a negative electrode plate, a separator interposed between the positive and negative electrode plates, and an electrolyte. The electrolyte contains sulfuric acid. Charging and discharging proceed through the movement of sulfate ions between the positive and negative electrode plates and the electrolyte.

[0059] A positive electrode plate, a negative electrode plate, and a separator constitute an electrode group. The electrode group, together with the electrolyte, constitutes a cell. One electrode group constitutes one cell. A lead-acid battery (B) comprises one or more cells by comprising one or more electrode groups. There is no particular limit to the number of positive and negative electrode plates included in one electrode group. An electrode group comprising a lead-acid battery (B) according to this disclosure may include, for example, a total of 12 or more positive and negative electrode plates. Multiple electrode groups are usually housed in separate cell chambers and connected in series with one another.

[0060] The negative electrode plate includes a negative electrode current collector and a negative electrode material. The negative electrode material is a negative electrode active material that exhibits capacity through an oxidation-reduction reaction, and contains at least lead during charging and at least lead sulfate during discharging.

[0061] The positive electrode plate includes a positive electrode current collector and a positive electrode material. The positive electrode material is a positive electrode active material that exhibits capacity through oxidation-reduction reactions, and contains at least lead dioxide during charging and at least lead sulfate during discharge.

[0062] In this specification, the fully charged state of a liquid lead-acid battery is defined according to the definition in JIS D5301:2019. More specifically, in a water bath at 25°C ± 2°C, the 20-hour rate current I is charged until the terminal voltage (in volts) or the electrolyte density converted to 20°C shows a constant value with three significant figures for three consecutive 15-minute intervals. 20 Twice the current 2I 20 (Unit: A) The fully charged state of a lead-acid battery is defined as the state in which it has been charged. Note that the 20-hour rate current I 20 This refers to a current (A) that is 1 / 20th of the Ah value listed in the rated capacity. The value listed as the rated capacity is a value in Ah (ampere-hour). The unit of the current set based on the value listed as the rated capacity is A (ampere).

[0063] Furthermore, in the case of a valve-regulated lead-acid battery, a fully charged state is defined as a 20-hour rate current of 1 in an air chamber at 25°C ± 2°C. 20 5 times the current 5I 20 The battery was then charged at a constant current and voltage of 2.67V / cell (16.00V for a lead-acid battery with a nominal voltage of 12V), and the charging process was terminated when the total charging time reached 24 hours.

[0064] A fully charged lead-acid battery is a lead-acid battery that has been charged to its full capacity after chemical formation. The timing for charging a lead-acid battery to its full capacity can be immediately after chemical formation, or after a certain amount of time has passed since formation (e.g., 720 hours or less). For example, a lead-acid battery that has been chemically formed and is in use (preferably in the early stages of use) may be charged.

[0065] In this specification, a battery in its initial use refers to a battery that has not been used for very long and has not deteriorated much (for example, a battery that has been in use for less than 720 hours, including the time elapsed since chemical preparation).

[0066] The lead-acid battery (B) according to an embodiment of the present invention will be described in more detail below with reference to the drawings. However, the present invention is not limited to the following embodiments.

[0067] The following describes examples of components of a lead-acid battery (B).

[0068] Figure 1 shows the external appearance and part of the internal structure of a lead-acid battery 1 according to one embodiment. The lead-acid battery 1 comprises a battery case 12 that houses an electrode plate group 11 and an electrolyte (not shown). The inside of the battery case 12 is divided into a plurality of cell chambers 14 by a partition wall 13. Each cell chamber 14 houses one electrode plate group 11. The opening of the battery case 12 is closed with a lid 15 equipped with a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When replenishing water, the vent plug 18 is removed and the water is supplied. The vent plug 18 may also have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0069] Each electrode plate group 11 is constructed by stacking multiple negative electrode plates 2 and positive electrode plates 3 via separators 4. Here, a bag-shaped separator 4 that houses the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In the cell chamber 14 located at one end of the battery case 12, a negative electrode shelf 6 that connects multiple negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf 5 that connects multiple positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 on the outside of the lid 15. In the cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf 6, and a through connector 8 is connected to the positive electrode shelf 5. The negative electrode column 9 is connected to a negative electrode terminal 16 on the outside of the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 and connects the electrode plate groups 11 of adjacent cell chambers 14 in series. Lead alloy (NA) according to this disclosure may be used in at least one of the components comprising lead alloy (NA), namely the positive electrode shelf 5, negative electrode shelf 6, positive electrode column 7, through connector 8, negative electrode column 9, negative electrode terminal 16, and positive electrode terminal 17.

[0070] Note that Figure 1 is merely an example of a liquid-type lead-acid battery, and the structure of the lead-acid battery (B) according to this disclosure is not limited to the example shown in the figure. Furthermore, the following description does not limit the configuration of the lead-acid battery (B) according to the present invention.

[0071] (Negative electrode plate) The negative electrode plate of a lead-acid battery (B) consists of a negative electrode current collector and a negative electrode material. The negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector. In some cases, an adhesive member may be attached to the negative electrode plate. In this case, the adhesive member is included in the negative electrode plate. When the negative electrode plate includes an adhesive member, the negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector and the adhesive member.

[0072] The negative electrode current collector included in the negative electrode plate may be formed by casting lead (Pb) or lead alloy (NA), or by processing a lead or lead alloy sheet. Examples of processing methods include expanding or punching. Using a grid-shaped current collector as the negative electrode current collector is preferable because it makes it easier to support the negative electrode material.

[0073] The lead alloy used for the negative electrode current collector may be any of the following: lead alloy (NA), Pb-Sb alloy, Pb-Ca alloy, or Pb-Ca-Sn alloy. The lead alloy (NA) may also be an alloy containing antimony (Sb), aluminum (Al), sodium (Na), silver (Ag), etc. The negative electrode current collector may have lead alloy layers of different compositions, and the alloy layer may be a single layer or multiple layers.

[0074] The negative electrode material contained in the negative electrode plate contains Pb. Pb is a negative electrode active material that exhibits capacity through oxidation-reduction reactions and is included in the negative electrode material as lead or lead sulfate.

[0075] The negative electrode material may further contain organic shrinkage inhibitors, carbonaceous materials, barium sulfate, reinforcing materials, and the like.

[0076] Examples of organic shrinkage inhibitors include lignin, lignin sulfonic acid, and synthetic organic shrinkage inhibitors (such as formaldehyde condensates of phenolic compounds). The content of the organic shrinkage inhibitor in the negative electrode material is, for example, 0.01% by mass or more. The content of the organic shrinkage inhibitor is, for example, 1.2% by mass or less.

[0077] Examples of carbonaceous materials include carbon black, graphite, hard carbon, and soft carbon. The carbonaceous material content in the negative electrode material is, for example, 0.1% by mass or more. The carbonaceous material content may also be, for example, 3.5% by mass or less.

[0078] The barium sulfate content in the negative electrode material is, for example, 0.1% by mass or more and 3% by mass or less.

[0079] Examples of reinforcing materials include fibers (inorganic fibers, organic fibers, etc.). The reinforcing material content in the negative electrode material is, for example, 0.03% by mass or more. Alternatively, the reinforcing material content in the negative electrode material is, for example, 0.6% by mass or less.

[0080] The negative electrode plate can be formed by filling a negative electrode current collector with negative electrode paste, aging and drying it to produce an unformed negative electrode plate, and then forming the unformed negative electrode plate. The negative electrode paste is made by kneading lead powder, an organic shrinkage inhibitor, barium sulfate, etc., with water and sulfuric acid. The negative electrode active material in the charged state is spongy lead, but the unformed negative electrode plate is usually made using lead powder. In the aging process, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at high humidity.

[0081] The chemical conversion can be carried out by immersing the electrode plate group, including the unconverted negative electrode plate, in the sulfuric acid-containing electrolyte in the lead-acid battery (B) case and then charging the electrode plate group. However, the chemical conversion may also be carried out before the assembly of the lead-acid battery (B) or the electrode plate group. Spongy lead is produced by the chemical conversion.

[0082] (Positive plate) For example, a paste-type positive electrode plate is used as the positive electrode plate. A paste-type positive electrode plate comprises a positive electrode current collector and a positive electrode material. The positive electrode material is held by the positive electrode current collector. The positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector. In addition, materials such as mats and pasting paper may be attached to the positive electrode plate. Since such attached materials are used integrally with the positive electrode plate, they are included in the positive electrode plate. When the positive electrode plate includes attached materials, the positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector and attached materials.

[0083] The positive electrode current collector included in the positive electrode plate may be formed by casting lead (Pb) or a lead alloy, or by processing a lead or lead alloy sheet. Examples of processing methods include expanding or punching. Using a grid-shaped current collector as the positive electrode current collector is preferable because it makes it easier to support the positive electrode material.

[0084] For the lead alloy used in the positive electrode current collector, the aforementioned lead alloy (NA) is used due to its corrosion resistance, mechanical strength, and high precipitation hardening (precipitation strengthening) phenomenon. The lead alloy (NA) may also be an alloy containing antimony (Sb), aluminum (Al), sodium (Na), silver (Ag), etc. The positive electrode current collector may have lead alloy layers of different compositions, and the alloy layer may be one layer or multiple layers. The mass content of Ca in the lead alloy (NA) is C Ca It may be 0.040% by mass or more and 0.080% by mass or less. From the viewpoint of obtaining a high effect of improving the mechanical strength of lead alloys, the mass content C Ca The amount is preferably 0.050% by mass or more and 0.080% by mass or less, and more preferably 0.050% by mass or more and 0.070% by mass or less.

[0085] The positive electrode material contained in the positive electrode plate includes a positive electrode active material (lead dioxide or lead sulfate) that exhibits capacity through oxidation-reduction reactions, and contains fibers as an additive. The positive electrode material may also contain other additives as needed.

[0086] The fiber content in the positive electrode material may be, for example, 0.01% by mass or more and 0.23% by mass or less, 0.02% by mass or more and 0.15% by mass or less, 0.03% by mass or more and 0.12% by mass or less, or 0.05% by mass or more and 0.10% by mass or less.

[0087] The effect of suppressing softening and shedding by fibers can also depend on the material of the fibers. Preferably, the fibers are made of a resin that is thin yet strong and stable in the presence of sulfuric acid.

[0088] The resin constituting the fiber may be polyester, polyolefin, polystyrene, polyvinyl chloride, acrylic resin, etc. Among these, at least one selected from the group consisting of polyester and polyolefin is preferred because of its excellent acid and alkali resistance. Examples of polyester include polyalkylene arylates such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). Examples of polyolefins include polyethylene, polypropylene (PP), and ethylene-propylene copolymer. The fiber may contain one of these resins or two or more. Furthermore, the positive electrode material may contain multiple fibers composed of different resins.

[0089] In particular, using PET makes it easier to improve the deep discharge life of lead-acid batteries (B). PET has excellent acid resistance and mechanical strength. Therefore, fibers made of PET have a fine average fiber diameter, and even in small quantities, they can secure a large surface area and sufficient durability, resulting in a significant improvement in the deep discharge life of lead-acid batteries (B). Furthermore, PET fibers are inexpensive.

[0090] For example, 85% or more of the fiber may be composed of polyester. Fibers containing such a high percentage of polyester are usually called polyester fibers (e.g., PET fibers). Alternatively, 85% or more of the fiber may be composed of polyolefin. Fibers containing such a high percentage of polyolefin are usually called polyolefin fibers (e.g., polyethylene fibers, polypropylene fibers). Similarly, fibers in which 85% or more of the fiber is composed of acrylic resin are called acrylic fibers.

[0091] The type of resin constituting the fibers contained in the positive electrode material can be identified by analyzing the fibers recovered from the positive electrode material using the method described in JIS L 1030-1:2024. The fibers may be recovered by pulling them out of the positive electrode material with tweezers, or they may be recovered from the residue after dissolving the lead compound contained in the positive electrode material, as described below.

[0092] The positive electrode material is recovered from the positive electrode plate by the following procedure. First, a fully charged lead-acid battery is disassembled, and the obtained positive electrode plate is washed with water for 3 to 4 hours to remove the electrolyte from the positive electrode plate. The washed positive electrode plate is dried in a constant temperature bath at 60°C ± 5°C for 5 hours or more. A bonding material containing fibers, such as a mat, and / or a nonwoven fabric separator may be attached to the positive electrode plate. The fibers contained in the bonding material and nonwoven fabric do not contain the fibers of the present invention. If a bonding material and / or nonwoven fabric is attached to the positive electrode plate, the surface of the positive electrode plate is scraped off until the residue of the bonding material and / or nonwoven fabric is removed, in order to prevent fibers derived from the bonding material and / or nonwoven fabric from contaminating the positive electrode material, before the positive electrode material is collected. For example, the residue may be evenly scraped off from the surface layers on both sides of the positive electrode plate before the positive electrode material is collected. At this time, it is desirable to scrape off a depth of about 0.1 mm to 0.3 mm on each side. Then, by taking a sample of the positive electrode material for analysis from near the center when viewing the positive electrode plate from the front, without crushing it, a sample of the positive electrode material can be obtained.

[0093] The fibers are recovered from the positive electrode material sample by the following procedure. First, a predetermined amount Wg (e.g., about 70g) of positive electrode material sample is crushed and accurately weighed. At this time, the positive electrode material contained in one or more positive electrode plates may be used as the sample.

[0094] Next, the pulverized sample is added to a mixed solution of acetic acid-sodium acetate solution and sodium thiosulfate solution (acetic acid concentration 1.7 mol / L, sodium acetate concentration 6.1 mol / L, sodium thiosulfate concentration 0.5 mol / L), and the soluble components are dissolved while stirring at room temperature. After that, the resulting residue is filtered using a membrane filter (average pore size: 0.45 μm or less). This allows the fibers contained in the positive electrode material to be obtained as solid matter on the filter paper.

[0095] A fiber sample for analysis is obtained by washing and drying the resulting solid. The mass w of the fiber sample is measured. The percentage of the mass w of the fiber sample relative to the mass W of the positive electrode material sample is the fiber content in the positive electrode material.

[0096] The resin constituting the fibers can be identified by analyzing the infrared absorption spectrum of the fiber sample. Method B (film method) specified in JIS L 1030-1:2024 may be used as the analytical method.

[0097] Specifically, the fiber sample is dissolved in an appropriate dissolving reagent (see Table A), poured into an evaporating dish, and dried under vacuum or by heating to a temperature that does not decompose the sample. Next, the dried film is peeled off without tearing, cut to an appropriate size, and the infrared absorption spectrum is measured in accordance with JIS K 0117:2017. The film should be of a thickness that makes it transparent. Also, the size of the film will vary depending on the infrared spectrophotometer used, so it should be at least 1 cm. 2 That concludes this section.

[0098] Table A exemplifies the main absorption bands and characteristic wavenumbers of the infrared absorption spectra of various fibers, as well as the dissolving reagents. The absorption bands and characteristic wavenumbers of each fiber vary by ±20 cm depending on the infrared spectrophotometer used. -1 There are differences in degree.

[0099] [Table A]

[0100] The average fiber diameter D of a fiber is determined by selecting any 20 fibers from a fiber sample, measuring the fiber diameter (the dimension perpendicular to the length of the fiber) at any point on each fiber, and taking the arithmetic mean of the measurements. The average fiber diameter D of a fiber may also be measured using a scanning electron microscope (SEM) image of the fiber.

[0101] Unformed paste-type positive electrode plates are obtained by filling a positive electrode current collector with positive electrode paste, followed by maturation and drying. The positive electrode paste is prepared by kneading lead powder, and optionally additives (fibers, antimony trioxide, etc.) with water and sulfuric acid.

[0102] A positive electrode plate can be obtained by chemically treating an untreated positive electrode plate. Chemical treatment can be carried out by immersing the electrode plate group, including the untreated positive electrode plate, in an electrolyte containing sulfuric acid in the battery case of a lead-acid battery (B), and then charging the electrode plate group. However, chemical treatment may also be carried out before the assembly of the lead-acid battery (B) or the electrode plate group.

[0103] (Separator) As a separator placed between the negative electrode and the positive electrode, at least one selected from, for example, nonwoven fabric and microporous membrane can be used.

[0104] Nonwoven fabrics are mats composed of interwoven fibers rather than woven fibers, and are primarily fiber-based. For example, 60% or more of the nonwoven fabric is made up of fibers. Suitable fibers include glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (such as polyethylene terephthalate fibers), etc.), and pulp fibers. Glass fibers are preferred among these. Nonwoven fabrics may also contain other components besides fibers, such as acid-resistant inorganic powders and polymers as binders.

[0105] A microporous membrane is a porous sheet mainly composed of non-fibrous components. For example, it can be obtained by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. Microporous membranes are preferably composed of acid-resistant materials, and preferably mainly composed of polymer components. Polyolefins (such as polyethylene and polypropylene) are preferred as polymer components. Examples of pore-forming agents include polymer powders and oils.

[0106] The separator may consist solely of a nonwoven fabric, or solely of a microporous membrane. The separator may also be a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same type of material bonded together, or a laminate of different or the same type of material with interlocking protrusions and indentations.

[0107] The separator may be in the form of a sheet or a bag. A single sheet-shaped separator may be placed between the positive and negative electrodes. The electrode plates may be sandwiched between folded sheet-shaped separators. The positive electrode sandwiched between folded sheet-shaped separators and the negative electrode sandwiched between folded sheet-shaped separators may be stacked on top of each other, or one of the positive and negative electrodes may be sandwiched between folded sheet-shaped separators and stacked on top of the other electrode plate. When a bag-shaped separator is used, the bag-shaped separator may contain either the positive electrode or the negative electrode.

[0108] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid. The electrolyte may be gelled if necessary.

[0109] The electrolyte may further contain at least one metal ion selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.

[0110] The specific gravity of the electrolyte at 20°C is, for example, 1.10 or higher. The specific gravity of the electrolyte at 20°C may also be 1.35 or lower. These specific gravity values ​​are for the electrolyte of a fully charged lead-acid battery (B).

[0111] The matters described herein can be combined in any way.

[0112] [Examples] The present invention will be described in detail below based on examples and comparative examples, but the present invention is not limited to the following examples. Here, a liquid lead-acid battery (B) with a nominal voltage of 12V and a 5-hour rate capacity of 30Ah is assembled. The 5-hour rate capacity is the capacity when discharged at a current (A) of 1 / 5 of the Ah value stated in the rated capacity.

[0113] [Evaluation Method] (Life Test Method) The deep discharge life will be evaluated in accordance with JIS D5301 (2019). Here, a fully charged lead-acid battery with a rated voltage of 12V will be repeatedly discharged and charged under the following conditions, and the number of deep discharge cycles until the deep discharge life is reached will be evaluated.

[0114] In the life test, regardless of the difference in the 20-hour rate capacity of the test batteries, the procedure is carried out according to (a) to (e) below. Here, the 20-hour rate capacity is the capacity when discharged to the discharge termination voltage at a current (A) of 1 / 20 of the Ah value stated in the rated capacity. The steps (a) to (e) below are carried out in the gas phase at 75℃±2℃.

[0115] (a) Discharge: Discharge at a current of 25A for 240 seconds. (b) Charging: Charge at a constant voltage of 14.8V for 600 seconds (however, the maximum current is 100A). (c) Repeat: Repeat steps (a) and (b) above 480 times, with each step counting as one cycle. (d) Take a break for 40 to 60 hours. (e) Determination discharge: After (d) above, discharge for 30 seconds at the rated cold cranking current Icc specified in JIS D5301 (2019). The point at which the voltage drops to 7.2V 30 seconds after the start of discharge is considered the end of the life cycle, and the number of cycles until the end of the life cycle is defined as the life cycle count.

[0116] Since discharge with the rated cold cranking current Icc is performed every 480 cycles, the number of cycles at which the voltage at 30 seconds reaches 7.2V can be determined by linear interpolation from a graph with the vertical axis representing the voltage at 30 seconds during the Icc discharge and the horizontal axis representing the number of cycles, and this can be used as the life cycle count.

[0117] Examples 1-17, Comparative Examples 1-13 (Batteries E1~E17, batteries C1~C13) (1) Fabrication of the positive electrode plate A positive electrode paste is prepared by mixing lead oxide, fibers, water, and sulfuric acid. The positive electrode paste is filled into the mesh of an expanded grid, which is a positive electrode current collector made of lead alloy (NA), and then aged and dried to obtain an unformed positive electrode plate with a width of 100 mm, a height of 110 mm, and a thickness of 1.6 mm. The fiber content in the positive electrode material, as measured by the method described above, is 0.07% by mass.

[0118] The resins that make up the fibers used in the positive electrode paste are as follows: Batteries E1-E14 and C1-C13 use PET, battery E15 uses acrylic resin, and battery E16 uses PP. In Table 1, "PET" refers to polyethylene terephthalate fiber, "acrylic" refers to acrylic fiber, and "PP" refers to polypropylene fiber.

[0119] The average fiber diameter of the fibers used in the positive electrode paste is as shown in Table 1.

[0120] In the lead alloy (NA) used for the positive electrode current collector, the mass content of Ca is C Ca 0.05 mass%, Sn mass content C Sn 1.6% by mass, Bi mass content C Bi Adjust the amount to less than 0.03% by mass. (Na mass content C) Na Adjust as shown in Table 1.

[0121] The number of Na-Sn compound particles (indicated as "Na-Sn count" in Table 1) and the particle size of the Na-Sn compound particles (indicated as "Na-Sn particle size" in Table 1) in lead alloy (NA) are confirmed or measured by SEM-EDS. In this case, the presence of Na-Sn compounds was not confirmed in batteries C1 to C12.

[0122] The particle size of intermetallic compounds can be controlled by the heat treatment method (rapid cooling, slow cooling, etc.) used during lead alloy slab formation. The more rapidly the mixture is cooled, the smaller the particle size of the intermetallic compounds becomes. The number of intermetallic compound particles can be controlled by the number of times the molten lead alloy is stirred. The more times it is stirred, the more intermetallic compound particles are produced.

[0123] (2) Fabrication of the negative electrode plate A negative electrode paste was prepared by mixing lead oxide, carbon black, barium sulfate, lignin, water, and sulfuric acid. The negative electrode paste was filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy, which served as the negative electrode current collector. By aging and drying, an unformed negative electrode plate with a width of 100 mm, a height of 110 mm, and a thickness of 1.3 mm was obtained. The Pb-Ca-Sn alloy used for the negative electrode current collector may contain sodium, but a Pb-Ca-Sn alloy that is substantially sodium-free was used here.

[0124] The amounts of carbon black, barium sulfate, and lignin used are adjusted so that the content of each component in the negative electrode plate removed from a fully charged lead-acid battery (B) is 0.3% by mass, 2.1% by mass, and 0.1% by mass, respectively.

[0125] (3) Manufacturing of lead-acid battery (B) Untreated negative electrode plates are housed in a bag-shaped separator made of a microporous polyethylene membrane, and stacked with positive electrode plates to form an electrode plate group consisting of seven untreated negative electrode plates and six untreated positive electrode plates.

[0126] The tabs of the positive electrode plate and the tabs of the negative electrode plate are welded to the positive and negative electrode trays, respectively, using the cast-on-strap (COS) method. The 6-cell electrode assembly is inserted into a polypropylene battery case, connected in series, electrolyte is poured in, and chemical conversion is performed within the battery case to assemble a liquid lead-acid battery (B) with a nominal voltage of 12V and a 5-hour rate capacity of 30Ah.

[0127] A sulfuric acid aqueous solution was used as the electrolyte. The density of the electrolyte after chemical conversion at 20°C was 1.285 g / cm³. 3 That is the case.

[0128] (4) Evaluation The life test of the obtained lead-acid battery (B) was performed and evaluated according to the procedure described above. Table 1 shows the relative values ​​of the deep discharge life for each example. The relative values ​​are the relative values ​​(%) when the deep discharge life of battery C1 in Comparative Example 1 is set to 100%.

[0129] [Table 1]

[0130] Table 1 shows that using a lead-acid battery (B) with an average fiber diameter of 16 μm or less and in which Na forms an intermetallic compound improves battery life. Furthermore, when Na forms an intermetallic compound, it is confirmed that the smaller the average fiber diameter, the more significantly the battery life improves. In batteries C1 to C6, where the positive electrode current collector does not contain Na, the deep discharge life of the battery improves as the average fiber diameter decreases. This is thought to be because, since there is no Na deposition, the fibers are not subjected to corrosion by alkali, and therefore fiber thinning does not occur. On the other hand, in batteries C7 to C12, which contain Na but in which no Na-Sn compound is formed, it is confirmed that the deep discharge life does not improve even when the average fiber diameter decreases. This is thought to be because, since no Na-Sn compound is formed in the positive electrode current collector, Na deposition is not suppressed.

[0131] Within the range where the number of Na-Sn compound particles present at each grain boundary is less than 10, it has been confirmed that the lifespan performance improves significantly as the number of particles increases. This is thought to be because the precipitation strengthening (precipitation hardening) effect by Na in the lead alloy (NA) becomes stronger. On the other hand, when the number of Na-Sn compound particles present at each grain boundary is 10 or more, a tendency for the effect of improving lifespan performance to decrease has been observed. This is thought to be because metallic Na precipitates on the surface of the lead alloy, accelerating the deterioration of the fibers.

[0132] Within the particle size range of 600 nm or less for Na-Sn compounds, it has been confirmed that the lifespan performance improves significantly as the particle size increases. This is thought to be because the precipitation hardening effect of Na in the lead alloy (NA) becomes stronger. On the other hand, it has been confirmed that when the particle size of Na-Sn compounds becomes excessively large, the effect of improving lifespan performance saturates and the effect of improving lifespan performance decreases. This is thought to be because intergranular corrosion of the lead alloy is accelerated.

[0133] It was confirmed that good deep discharge life can be obtained regardless of whether PET fiber, acrylic fiber, or PP fiber is used as the resin for the fibers. The improvement in lifespan performance is greatest with PET fiber, followed by PP fiber and then acrylic fiber. [Industrial applicability]

[0134] The lead-acid battery according to this disclosure is suitable, for example, as a lead-acid battery for vehicles employing a start-stop system, and can also be suitably used as a power source for industrial energy storage devices such as electric vehicles (forklifts, etc.). These applications are merely examples. The applications of the lead-acid battery according to the present invention are not limited to these. [Explanation of symbols]

[0135] 1: Lead-acid battery, 2: Negative electrode plate, 3: Positive electrode plate, 4: Separator, 5: Positive electrode shelf, 6: Negative electrode shelf, 7: Positive electrode column, 8: Through connector, 9: Negative electrode column, 11: Electrode plate group, 12: Battery case, 13: Partition wall, 14: Cell chamber, 15: Cover, 16: Negative electrode terminal, 17: Positive electrode terminal, 18: Electrode cap< / eds>

Claims

1. It comprises a positive electrode plate, a negative electrode plate, an electrolyte, and a separator interposed between the positive electrode plate and the negative electrode plate. The positive electrode plate includes a positive electrode current collector and a positive electrode material. The positive electrode current collector is made of a lead alloy containing Ca, Sn, and Na. At the grain boundaries of the crystal grains constituting the lead alloy, the Na forms an intermetallic compound. The positive electrode material includes fibers, A lead-acid battery in which the average fiber diameter of the aforementioned fibers is 16 μm or less.

2. The lead-acid battery according to claim 1, wherein the average fiber diameter of the aforementioned fibers is 10 μm or less.

3. The lead-acid battery according to claim 1, wherein the average fiber diameter of the aforementioned fibers is 1 μm to 8 μm.

4. The surface of the aforementioned fiber has irregularities, The lead-acid battery according to any one of claims 1 to 3, wherein the irregularities are formed along the circumferential direction of the fibers.

5. The lead-acid battery according to claim 1, wherein the intermetallic compound comprises a Na-Sn compound.

6. The lead-acid battery according to claim 5, wherein at least three particles of the Na-Sn compound are detected around the grain boundary of one crystal grain observed in the cross-section of the lead alloy.

7. The lead-acid battery according to claim 6, wherein the particle size of the Na-Sn compound particles is 50 nm or more and 800 nm or less.

8. The mass content C of the Na contained in the lead alloy Na The lead-acid battery according to claim 5, wherein the concentration is 10 ppm or more and 100 ppm or less.

9. The lead alloy either does not contain Bi, or if it does, the mass content of Bi C Bi The lead-acid battery according to claim 5, wherein the amount is less than 0.03% by mass.

10. The mass content C of Sn contained in the lead alloy Sn The lead-acid battery according to claim 5, wherein the amount is 1.5% by mass or more and 2.5% by mass or less.

11. The lead-acid battery according to claim 1, wherein the positive electrode current collector is an expanded grid.

Citation Information

Patent Citations

  • Lead storage battery

    JP2019067741A

  • Expanded grid of lead-acid battery

    JP3036235B2